Transactions on Engineering Technologies Special Issue of the World Congress on Engineering and Computer Science 2013 - Kim, Haeng Kon; Ao, Sio-Iong; Amouzegar, Mahyar A. (Springer Netherlands : Imprint: Springer, 2014)
This volume contains fifty-six revised and extended research articles, written by prominent researchers participating in the congress. Topics covered include electrical engineering, chemical engineering, circuits, computer science, communications systems, engineering mathematics, systems engineering, manufacture engineering, and industrial applications. This book offers theoretical advances in engineering technologies, and presents state of the art applications. It also serves as an excellent source of reference for researchers and graduate students working with/on engineering technologies.